Contentment (Qana'ah) and its role in curbing social and environmental problems - Ali, Mohammed Farid (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
Contentment is an important dimension of virtuous human character (akhlaq) in the context of our attitude towards material provision and worldly sustenance, and our attitude towards sharing our sustenance with others. We first explore the position which the discipline of cultivating human character holds in Islam. It discloses the direct relationship of human character with our society and the environment. These relations are the foundation on which the treatment of contentment (qana'ah) is based. After defining the term qana'ah, we discuss the “good wholesome life (hayatan tayyibah)” mentioned in the Qur’an (al-Nahl 16:97) which denotes ‘self-contentment’. The term provides the premise that a virtuous and pure life in this world is based on human selfcontrol towards his means of provision, his society, and the environment. With a disciplined human attitude towards material means, material abundance or scarcity of worldly things will not disrupt one’s conviction and self-sufficiency. We then discuss the by-products of non-contentment and greed such as wasting of food and other natural resources. This leads us to the topic of self-discipline in terms of dealing with the material world and our fellows. Finally we discuss the importance of self-discipline through frugal- moderation for individual and civilisational renewal.